Randomized pharmacokinetic and drug–drug interaction studies of ceftazidime, avibactam, and metronidazole in healthy subjects. Issue 5 (25th August 2015) - Das, Shampa; Li, Jianguo; Armstrong, Jon; Learoyd, Maria; Edeki, Timi
Abstract: We assessed pharmacokinetic and safety profiles of ceftazidime–avibactam administered ± metronidazole, and whether drug–drug interactions exist between ceftazidime and avibactam, or ceftazidime‐avibactam and metronidazole. The first study (NCT01430910) involved two cohorts of healthy subjects. Cohort 1 received ceftazidime–avibactam (2000–500 mg) as a single infusion or as multiple intravenous infusions over 11 days to evaluate ceftazidime–avibactam pharmacokinetics. Cohort 2 received ceftazidime, avibactam, or ceftazidime–avibactam over 4 days to assess drug–drug interaction between ceftazidime and avibactam. The second study (NCT01534247) assessed interaction between ceftazidime–avibactam and metronidazole in subjects receiving ceftazidime–avibactam (2000–500 mg), metronidazole (500 mg), or metronidazole followed by ceftazidime–avibactam over 4 days. In all studies, subjects received a single‐dose on the first and final days, and multiple‐doses every 8 h on intervening days. Concentration‐time profiles for ceftazidime and avibactam administered as single‐ or multiple‐doses separately or together with/without metronidazole were similar. There was no evidence of time‐dependent pharmacokinetics or accumulation. In both interaction studies, 90% confidence intervals for geometric least squares mean ratios of area under the curve and maximum plasma concentrations for each drug were within the predefined interval (80–125%) indicating no drug–drug interaction between ceftazidime and avibactam, or ceftazidime–avibactam and metronidazole. There were no safety concerns. In conclusion, pharmacokinetic parameters and safety of ceftazidime, avibactam, and metronidazole were similar after single and multiple doses with no observed drug–drug interaction between ceftazidime and avibactam, or ceftazidime–avibactam and metronidazole.